ICoRD'15 - research into design across boundaries volume 1 : theory, research methodology, aesthetics, human factors and education - Chakrabarti, Amaresh (Smart Innovation, Systems and Technologies,, 2015)
This book showcases cutting-edge research papers from the 5th International Conference on Research into Design - the largest in India in this area - written by eminent researchers from across the world on design process, technologies, methods and tools, and their impact on innovation, for supporting design across boundaries. The special features of the book are the variety of insights into the product and system innovation process, and the host of methods and tools from all major areas of design research for the enhancement of the innovation process. The main benefit of the book for researchers in various areas of design and innovation are access to the latest quality research in this area, with the largest collection of research from India. For practitioners and educators, it is exposure to an empirically validated suite of theories, models, methods and tools that can be taught and practiced for design-led innovation.